From waste to wealth: Utilisation of marine based shell waste in producing hydroxyapatite for biomedical applications - Shariffuddin, Jun Haslinda
Bio-scaffold is referred to an artificial structure that being used alternatively as bone replacement for bone tissue regeneration. The ultimate objective of this study is to synthesis the bio-scaffold derived from the cockle shell waste. Main steps involved in the production of the scaffold including pre-treatment of cockle shells, synthesis of Hydroxyapatite (HAP) and synthesis of bio-scaffold. The scaffolds were then undergone physicochemical and mechanical characterization to identify their functional groups, surface morphology, elemental components and compressive strength. Bioactivity of scaffolds evaluated by immersing them in the simulated body fluid solution (SBF). Overall, it is feasible to produce CaCO3 from cockle shell wastes as the results obtained shows the physicochemical characteristic of the cockle shell powder imitated the real CaCO3. Furthermore, HAP also significantly produced from cockle shell waste since cockle shells are rich with calcium source. Then, it is proved that all the prepared scaffolds produced has similar properties as actual bone in term of physicochemical, mechanical properties and bioactivity.